2020
DOI: 10.1002/pi.6133
|View full text |Cite
|
Sign up to set email alerts
|

A novel preparation method of polypropylene/natural rubber blends with improved toughness

Abstract: A novel melt compounding methodoriginally introduced for the preparation of nanocompositeswas adapted to produce polypropylene (PP) based blends toughened with up to 20 wt% natural rubber (NR). This water-assisted technique is based on batchwise melt mixing, where the additives are introduced as an aqueous dispersion into the matrix, drop by drop. The efficiency of this preparation technique was analyzed by comparing the resulting blends with reference samples produced by traditional melt mixing. Mechanical, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Unlike the unobvious change in the POE particle size and microstructure in PP/POE, many particles (2–5 μm) appeared on the fracture surface in PP/POE/ r PP when the mold temperature increased from 23 to 60°C. As revealed by the above study, the increased phase separation resulted in a lower elongation at break 33 …”
Section: Resultsmentioning
confidence: 55%
“…Unlike the unobvious change in the POE particle size and microstructure in PP/POE, many particles (2–5 μm) appeared on the fracture surface in PP/POE/ r PP when the mold temperature increased from 23 to 60°C. As revealed by the above study, the increased phase separation resulted in a lower elongation at break 33 …”
Section: Resultsmentioning
confidence: 55%
“…The blending of elastomers and plastics has become a widely adapted, simple, and cost-effective method to generate industrially important raw materials with combined characteristics of component polymers. [20][21][22][23][24][25][26][27] The blending of NR with various thermoplastic materials forms an industrially important class of continuous or multi-phase materials known as Thermoplastic Natural Rubber (TPNR). A large number of studies is found in the literature on TPNR and its composites produced using different NR types such as ribbed smoked sheets (RSS), technically specified rubber (TSR), etc., and different thermoplastics (TPs) such as polyethylene (PE), polypropylene (PP), etc.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous reduction of fossil fuel due to heavy consumption by industries has made it necessary to bring forward renewable sources as much as possible to meet the daily power demand. [1][2][3] Wind energy, a renewable energy source, produces nearly 2% of the total power generated by fossil fuels. [4] The worldwide power generation by wind energy was estimated at 591 GW, in which India stands at fourth position with the wind power generation of 35.1 MW.…”
Section: Introductionmentioning
confidence: 99%